A Convenient Method for Manufacturing TiO2 Electrodes on Titanium Substrates - Wei Qin; Songtao Lu; Xiaohong Wu; Song Wang (International Journal of Photoenergy)
Thin titanium dioxide films were successfully prepared on titanium plates in ammonium sulfate solution with the micro-plasma oxidation method. The thin TiO2 films were sensitized with a cis-RuL2(SCN)2⋅2H2O (L = cis-2, 2′-bipyridine-4, 4′-dicarboxlic acid) ruthenium complex, and implemented into a dye sensitized solar cell configuration. The influence of current density on the surface structure and photoelectric performance of the TiO2 films was investigated. The results show that the thin TiO2 films are porous, and the dye-sensitized solar cell based on the film prepared at 14 A/dm2 has exhibited higher overall light-to-electricity conversion efficiencies of 0.095% under the illumination at 40 mW/cm2.